QUANTIFICATION OF SELECTED ANTIBIOTICS IN HUMAN URINE AND EXPOSURE-RESPONSE OF WHEAT TO ENVIRONMENTALLY RELEVANT CONCENTRATIONS - Alfred Ndorwu Barnett; Rabeea Zafar; Samreen Akhter; Deedar Nabi; Muhammad Arshad (Journal of Animal and Plant Sciences, 2025)
Soil health is critical for food security and safety, but different sources of pollutants permanently threaten it. Eco-sanitation products like human urine can contribute to the antibiotic burden of soil and consequently affect plant growth. This study aimed to assess the prevalence of five commonly used antibiotics in human urine and the effects of ciprofloxacin on wheat upon exposure to environmentally relevant concentrations. Antibiotics were extracted from the eco-sanitation product (urine) using a liquid-liquid extraction process and analyzed using high-performance liquid chromatography (HPLC). Wheat seeds (n = 15) were treated with ciprofloxacin concentrations (1-50 µg/mL) at an exposure time of 24, 48, and 72 h to assess the effect on seed germination, biomass, root, and shoot lengths. The highest mean concentration in urine was observed for ciprofloxacin (21.24 ± 9.50 µg/mL), followed by sulfamethoxazole (6.47 ± 0.48 µg/mL), levofloxacin (2.91 ± 0.23 µg/mL), and oxytetracycline (1.86 ± 0.26 µg/mL), while the lowest was observed for ofloxacin (1.23 ± 0.45 µg/mL). A significant difference was observed among the means at P ≤ 0.05. Wheat germination did not show any significant effect upon exposure. The results also showed time and dose-dependent decreases in wheat biomass, root, and shoot lengths. At 48 h and 72 h exposures, the biomass decreased from 0.90 g to 0.40 g and from 1.30 g to 0.70 g with an increase in concentrations from 1 µg/mL to 50 µg/mL, respectively. The root length showed a decrease of 14% to 45% (24 h), 18% to 60% (48 h), and 16% to 63% (72 h) at ciprofloxacin concentrations of 1 to 50 µg/mL, respectively. The shoot length also decreased from 0% to 33% in 24 h, 0% to 14% in 48 h, and 3.0% to 22% in 72 h at a concentration range of 1 to 50 µg/mL, respectively. Antibiotic residues in humans and the phytotoxic effect on wheat can potentially harm plant growth and introduce risks to human health; therefore, public awareness is essential to promote responsible antibiotic use to safeguard human health and the environment.
Keywords: Antibiotics; wheat; phytotoxicity; liquid-liquid extraction